2014
DOI: 10.1039/c4dt00261j
|View full text |Cite
|
Sign up to set email alerts
|

Bis(2-quinolylmethyl)ethylenediaminediacetic acids (BQENDAs), TQEN–EDTA hybrid molecules as fluorescent zinc sensors

Abstract: Molecular hybrids of TQEN (N,N,N',N'-tetrakis(2-quinolylmethyl)ethylenediamine) and EDTA (ethylenediamine-N,N,N',N'-tetraacetic acid) were examined as fluorescent Zn(2+) sensors. Upon the addition of Zn(2+), N,N-BQENDA (N,N-bis(2-quinolylmethyl)ethylenediamine-N',N'-diacetic acid, 1a) exhibits a 30-fold emission enhancement at 456 nm (λex = 315 nm, ϕZn = 0.018) in buffer (HEPES, pH = 7.5, 100 mM KCl). The fluorescence enhancement is Zn(2+)-specific as Cd(2+) induces much smaller increases (ICd/I0 = 5 and ICd/I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Our previous investigation revealed that the long fluorescence lifetime were suggestive of excimer emission. [37][38][39][40][41] As discussed in our previous communication, [36] the long lifetime of TQLNÀ Zn 2 + is an indication of intramolecular excimer emission and short lifetime of 1-isoTQLNÀ Cd 2 + complex suggests the monomer emission based on CHEF and inhibition of PeT. [42] Table summarizes the data from fluorescence lifetime measurement and other fluorescence properties of TQLN derivatives.…”
Section: Complexes Of Tqln 1-isotqln and 3-isotqlnmentioning
confidence: 89%
See 1 more Smart Citation
“…Our previous investigation revealed that the long fluorescence lifetime were suggestive of excimer emission. [37][38][39][40][41] As discussed in our previous communication, [36] the long lifetime of TQLNÀ Zn 2 + is an indication of intramolecular excimer emission and short lifetime of 1-isoTQLNÀ Cd 2 + complex suggests the monomer emission based on CHEF and inhibition of PeT. [42] Table summarizes the data from fluorescence lifetime measurement and other fluorescence properties of TQLN derivatives.…”
Section: Complexes Of Tqln 1-isotqln and 3-isotqlnmentioning
confidence: 89%
“…The present results provide valuable information for future molecular design of fluorescent probes for specific metal ions and other small molecules. Development of water-soluble derivatives [33,40,45] is also under investigation in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…stronger metal bonding affinity, the sensor has higher selectivity towards Zn 2+ detection [84]. It is crucial to keep in mind that fluorescent groups with lone pairs of electrons like nitrogen will be quenching the emission.…”
Section: Aminoquinoline As a Fluorophore For Zinc's Recognitionmentioning
confidence: 99%
“…Figure 4c showed, under the same condition, the emission of N, N-BQENDA-Zn is more enhanced than the emission of TQEN-Zn. With the stronger metal bonding affinity, the sensor has higher selectivity towards Zn 2+ detection [84].…”
Section: Aminoquinoline As a Fluorophore For Zinc's Recognitionmentioning
confidence: 99%
“…In order to deeply understand the crucial role of Zn 2+ in important life processes, large amounts of Zn 2+ uorescent sensors have been accepted and effectively applied in vivo. [19][20][21][22][23][24] Among the reported uorescent chemosensors for detecting Zn 2+ , [25][26][27][28] diarylethenes are considered one of the most potential candidates due to their remarkable fatigue resistance, excellent thermal stability, rapid response and multi-responsively photoswitchable properties under various stimulations. [29][30][31][32] To date, numerous diarylethene-based uorescent sensors with various functional groups have been developed for the detection of Zn 2+ .…”
Section: Introductionmentioning
confidence: 99%